Effects of B(2)O(3) on Melting Characteristics and Temperature-Dependent Viscosity of High-Basicity CaO–SiO(2)–FeO(x)–MgO Slag - Chong, Junkai (Materials (Basel), 2020)
In order to reduce the amount of fluorite during the steelmaking process for environmental protection, it is essential to investigate the fluorine-free slag system. Thus, high-basicity CaO–SiO(2)–FeO(x)–MgO slag with B(2)O(3) content from 0% to 15% was designed, and its melting characteristics and viscosity were investigated. The influence of B(2)O(3) content on the phase diagram of the slag system was calculated using FactSage 7.3, and the break temperature was determined from the curves of temperature-dependent viscosity. The results show that, with the increase in B(2)O(3) content, the melting characteristics of the CaO–SiO(2)–FeO(x)–MgO/B(2)O(3) slag system, including liquidus temperature, flow temperature, softening temperature, and hemispheric temperature, all decreased; the main phase of the slag system transformed from Ca(2)SiO(4) into borosilicate, and finally into borate; the viscous flow activation energy reduced from 690 kJ to 130 kJ; the break temperature reduced from 1590 °C to 1160 °C. Furthermore, the melting characteristics and the break temperature of the slag system with 5% and 8% B(2)O(3) content were found to be the closest to the values of fluorine-containing steel slag.